Transformations of PTCDA structures on rutile TiO2 induced by thermal annealing and intermolecular forces - Godlewski, Szymon; Prauzner-Bechcicki, Jakub S.; Glatzel, Thilo; Meyer, Ernst; Szymoński, Marek (Beilstein Journal of Nanotechnology, 2015)
Transformations of molecular structures formed by perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) molecules on a rutile TiO2(110) surface are studied with low-temperature scanning tunnelling microscopy. We demonstrate that metastable molecular assemblies transform into differently ordered structures either due to additional energy provided by thermal annealing or when the influence of intermolecular forces is increased by the enlarged amount of deposited molecules. Proper adjustment of molecular coverage and substrate temperature during deposition allows for fabrication of desired assemblies. Differences between PTCDA/TiO2(110) and PTCDA/TiO2(011) systems obtained through identical experimental procedures are discussed.
Keywords: PTCDA, TiO2, rutile, self-assembly, STM